Antioxidant Activity Test of Sappan (Caesalpinia sappan L.) and Chinese Teak (Senna alexandrina) Extract Combination Using DPPH (1,1 Diphenyl 2 Picrylhydrazyl) Free Radicals Scavenging Method - Anisa, Rianti; Naid, Tadjuddin; Malik, Abd.; Nisaa, Nur Rezky Khairun (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
Sappan (Caesalpinia sappan L.) is applied as food and traditional medicine. Chinese teak (Senna alexandrina) is a plant from the tropics that can be developed as an antioxidant. This study was conducted to determine the antioxidant activity of the combination of Sappan and Chinese Teak by the DPPH (1,1 Diphenyl 2 Picrylhydrazyl) Free Radical Scavenging method. The extraction method used was maceration with Ethanol 96% as solvent. Determination of antioxidant levels was done quantitatively using the UV-Vis Spectrophotometer instrument at a wavelength of 514 nm. From the results of the study, the regression value obtained for the comparison of Quercetin is y = 3.1303x + 0.2292 with R2 = 0.9974 and IC50 value of 15.899 μg/mL. For the antioxidant activity of Sappan, the regression value y=0.5769x + 18.543 with R2=0.9969 and IC50 value of 54.53 μg/mL, Chinese Teak obtained regression value y=0.1421x + 17.506 with R2=0.9989 and IC50 value of 228.67 μg/mL, and for the combination obtained regression value y=0.4304x + 36.622 with R2=0.9954 and IC50 value of 40.38 μg/mL. The results of this study indicate that the combination of Sappan and Chinese Teak extracts has a very strong antioxidant effect (<50 μg/mL).